A practice-based approach to understanding learning on placement: identifying handholds and knowing how to go on. Issue 3 (2nd September 2022) - Dean, Bonnie Amelia; Sykes, Christopher
ABSTRACT: One of the key challenges in work-integrated learning (WIL) courses is how to account for learning that takes place away from campus, where the work space, daily routines and emergent actions within an organisation shape the possibilities for student learning. What do students do on placement to open the possibilities of working and learning in temporary sites of work? Using a practice-based approach, this paper outlines an ethnographic study of learning on placement. The paper draws on Gherardi's ([2019]. How to Conduct a Practice-Based Study: Problems and Methods . 2nd ed. Cheltnham: Edward Elgar Publishing) work on learning and knowing in practice to demonstrate how students learn to participate in situated practices to accomplish work tasks. It employs a rock-climbing metaphor to illuminate what students do in order to continue on with work when they encounter something surprising, make an error or have a question. The findings suggest student learning relies on the sociomaterial practices that produce and are produced by each unique workplace situation. The paper shows how learning on placement comprises the identification and use of distinct 'handhold' activities performed through simultaneous processes of knowing, doing and inventing.